Predictive factors of complications after robot‐assisted laparoscopic partial nephrectomy: a retrospective multicentre study. (23rd July 2013) - Mathieu, Romain; Verhoest, Gregory; Droupy, Stéphane; de la Taille, Alexandre; Bruyere, Franck; Doumerc, Nicolas; Rischmann, Pascal; Vaessen, Christophe; Roupret, Morgan; Bensalah, Karim
Abstract : Objective: To analyse the predictive factors of complications after robot‐assisted laparoscopic partial nephrectomy (RALPN). Materials and Methods: Data from six French institutions on 240 patients who underwent RALPN between 2009 and 2011 were retrospectively reviewed. Clinical (age, body mass index, American Society of Anesthesiologists and Charlson comorbidity index scores, anticoagulant treatment), tumoral (size, R.E.N.A.L nephrometry score) and operative (surgeon experience, blood loss, opening of the collecting system, operating time) variables were considered. Univariate and multivariate regression models were used to assess the impact of these variables on the occurrence of global and major postoperative complications, classified according to the Clavien system. Results: The median (range) patient age was 61 (26–83) years. Tumours were of low complexity in 62% of cases. Median (range) operating time, blood loss and warm ischaemia time were 161 (45–425) min, 100 (0–2500) mL and 20 (0–59) min, respectively. Postoperative complications occurred in 79 (33%) patients. Complications were ≥grade III in 25 (10%) patients and were mostly haemorrhagic. In multivariate analysis, surgeon's experience (hazard ratio [HR]: 2.14 [1.07–4.27], P = 0.03) and blood loss (HR: 1.002 [1.001–1.003], P < 0.001) were independent predictors of overall complications. When considering major complications, opening of the collecting system was the only factor that was significant (OR: 2.99 [1.2–7.26], P = 0.02). Nephrometry R.E.N.A.L. score was not associated with postoperative complications. Conclusion: In our experience, RALPN is associated with a 30% risk of postoperative complications; surgeon's experience, blood loss and opening of the collecting system were the three predictors of postoperative complications.